Trachoma and Ocular Chlamydial Infection in the Era of Genomics - Tamsyn Derrick; Chrissy h. Roberts; Anna R. Last; Sarah E. Burr; Martin J. Holland (Mediators of Inflammation)
Trachoma is a blinding disease usually caused by infection with Chlamydia trachomatis (Ct) serovars A, B, and C in the upper tarsal conjunctiva. Individuals in endemic regions are repeatedly infected with Ct throughout childhood. A proportion of individuals experience prolonged or severe inflammatory episodes that are known to be significant risk factors for ocular scarring in later life. Continued scarring often leads to trichiasis and in-turning of the eyelashes, which causes pain and can eventually cause blindness. The mechanisms driving the chronic immunopathology in the conjunctiva, which largely progresses in the absence of detectable Ct infection in adults, are likely to be multifactorial. Socioeconomic status, education, and behavior have been identified as contributing to the risk of scarring and inflammation. We focus on the contribution of host and pathogen genetic variation, bacterial ecology of the conjunctiva, and host epigenetic imprinting including small RNA regulation by both host and pathogen in the development of ocular pathology. Each of these factors or processes contributes to pathogenic outcomes in other inflammatory diseases and we outline their potential role in trachoma.